Identifying critical climate conditions for use in scenario-neutral climate impact assessments. (February 2021) - Culley, S.; Maier, H.R.; Westra, S.; Bennett, B.
Abstract: Scenario-neutral climate impact assessments are being used increasingly to assess water resource system responses to possible climate changes. The purpose of such assessments is to identify system sensitivity to a range of plausible climate conditions, often including an evaluation of the joint effect of multiple climate stressors. Given the large number of climate variables and associated statistics (averages, seasonality, intermittency, extremes, etc.) that could plausibly change and impact on system performance, it is essential that scenario-neutral assessments focus on those to which the system is most sensitive. A generic approach to identifying these 'critical' climate conditions is presented and tested on the Lake Como reservoir in Northern Italy considering two system objectives: irrigation deficit and flood reliability. Results indicate that different climate conditions are critical for the two objectives, and that the choice of which climate conditions to include has a significant effect on the climate impact assessment outcome. Key points: It is critical that scenario-neutral assessments consider climate conditions to which system performance is most sensitive. A generic approach is presented to enable such critical conditions to be identified and applied to a reservoir case study. Results demonstrate the utility of the approach as different attributes are critical for different objectives.